QUR’ANIC EDUCATIONAL VALUES IN KITAB KUNING TEACHING: A Living Qur’an Study - Babay Balya; Abdul Kosim; Tajuddin Nur; Muhammatkasibudi Hajimasamae (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2026)
This study aims to analyze the implementation of educational values in Q.S. At-Taubah verse 122 in Kitab Kuning teaching through the Living Qur’an perspective in a pesantren environment. The research focus is directed at the process of internalizing the values of tafaqquh fī ad-dīn and li yundzirū qawmahum in the pedagogical practices of traditional Islamic education. This study employs a qualitative approach with a field research design conducted at a Salafiyah pesantren that still maintains the tradition of intensive Kitab Kuning instruction. Research participants include pesantren administrators, Kitab Kuning instructors, and students actively engaged in learning activities. Data were collected through participant observation, in-depth interviews, and documentation of learning activities as well as students’ religious practices. Data analysis was conducted using the Miles and Huberman interactive model, which includes data reduction, data presentation, and interpretive conclusion-drawing to understand the process of transforming Qur’anic values in pesantren education. The research results indicate that the study of classical Islamic texts (kitab kuning) serves not only as a means of transmitting Islamic knowledge but also as a medium for the internalization of Qur’anic educational values encompassing spiritual, intellectual, moral, and social dimensions. The value of tafaqquh fī ad-dīn is realized through the tradition of deepening classical texts, fostering critical thinking, and the intellectual discipline of students, while the value of li yundzirū qawmahum is reflected in the development of da’wah responsibility, social service, and moral exemplary behavior within the community. The findings of this study affirm that the Living Qur’an approach offers a new perspective in Islamic education studies by demonstrating how Qur’anic verses are contextualized and sustainably actualized in pesantren educational practices. This research contributes to the development of pesantren-based Islamic education studies, particularly in understanding the integration of sacred texts, scholarly traditions, and the formation of students’ socio-religious character.